Confirmatory Factor Analysis and Internal Consistency of the Suicidal Ideation Scale of the Center for Epidemiological Studies Depression Among Colombian Adolescents (2020)
The current study tested the one-dimensionality of the Center for Epidemiological Studies Depression Scale for Suicidal Ideation (CES-D-SI) and its reliability among high school students in Santa Marta, Colombia. A total of 1,462 tenth and eleventh-grade students from public and private schools completed the CES-D-SI. The students were between 13 and 17 years (M = 16.0, SD = 0.8), 60.3% were female, and 55.3% were in the tenth grade. A confirmatory factor analysis (CFA) was conducted, and the chi-square, root mean square error of approximation (RMSEA), comparative fit index (CFI), Tucker-Lewis index (TLI), and standardized root mean square residual (SRMR) statistics were calculated. The internal consistency of the dimension was calculated using Cronbach’s alpha and McDonald’s omega coefficients. The results of the CFA were as follows: chi-square = 26.51, df =2, p = .001; RMSEA = .092; 90% confidence interval = .063–.124; CFI = .983; TLI = .950; and SRMR = .019. Cronbach’s alpha coefficient was .75, and McDonald’s omega coefficient was .77. As conclusions, the scale exhibited a unidimensional structure similar to that in other studies and presented good reliability values. Hence, its use is recommended to screen suicidal ideation in school-aged adolescents in Santa Marta, Colombia